2022
DOI: 10.1186/s12951-022-01706-0
|View full text |Cite
|
Sign up to set email alerts
|

Bio-nanocomplexes with autonomous O2 generation efficiently inhibit triple negative breast cancer through enhanced chemo-PDT

Abstract: As one kind of aggressive cancer, triple-negative breast cancer (TNBC) has become one of the major causes of women mortality worldwide. Recently, combinational chemo-PDT therapy based on nanomaterials has been adopted for the treatment of malignant tumor. However, the efficacy of PDT was partly compromised under tumor hypoxia environment due to the lack of sustainable O2 supply. In this study, CeO2-loaded nanoparticles (CeNPs) with peroxidase activity were synthesized to autonomously generate O2 by decomposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…In line with ndings of Wang et al [34] and Zhu et al [38], it was discovered that Fe 3 O 4 /MnO 2 @DOX hybrid nanozymes, particularly in synergistic activity, demonstrates substantial toxicity against MCF-7 cells by promoting apoptosis through enhanced ROS. Nevertheless, in agreement with the ndings of Nie et al [39] and Zeng et al [40], it was found that the Fe 3 O 4 /MnO 2 @DOX hybrid nanozymes, as opposed to DOX administration, could improve the treatment process by targeting of drug release, triggering intracellular ROS, and raising O 2 levels. This increase in the aforementioned events without synergistic effects by PTT could raise hopes for treating tumors inaccessible to laser irradiation.…”
Section: Discussionsupporting
confidence: 86%
“…In line with ndings of Wang et al [34] and Zhu et al [38], it was discovered that Fe 3 O 4 /MnO 2 @DOX hybrid nanozymes, particularly in synergistic activity, demonstrates substantial toxicity against MCF-7 cells by promoting apoptosis through enhanced ROS. Nevertheless, in agreement with the ndings of Nie et al [39] and Zeng et al [40], it was found that the Fe 3 O 4 /MnO 2 @DOX hybrid nanozymes, as opposed to DOX administration, could improve the treatment process by targeting of drug release, triggering intracellular ROS, and raising O 2 levels. This increase in the aforementioned events without synergistic effects by PTT could raise hopes for treating tumors inaccessible to laser irradiation.…”
Section: Discussionsupporting
confidence: 86%
“…Breast cancer (BC), the most prevalent malignant tumor globally, is characterized by significant heterogeneity 1 . It poses a considerable health risk to women 2–4 . Despite advances in early detection and treatment, drug resistance remains a primary obstacle, often leading to poor prognosis in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…1 It poses a considerable health risk to women. [2][3][4] Despite advances in early detection and treatment, drug resistance remains a primary obstacle, often leading to poor prognosis in various malignancies. The treatment methods for BC extend from surgical intervention to chemotherapy, radiotherapy, endocrine therapy, anti-HER2 therapy and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to late diagnosis and inefficiency of chemotherapy activities, surgery is considered the most important TNBC treatment strategy (Alsughayer et al 2022;Wang et al 2022). Nevertheless, the therapeutic hopes resulting from combined approaches such as the integration of chemotherapy with photo-therapy, thermal-therapy, radio-therapy, etc., have directed attention towards more non-invasive activities (Zeng et al 2022;Wu et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wu et al (2022) with synergy of PDT and chemo-therapy based on manganese oxide NZ containing doxorubicin not only improved drug delivery through modifying the membrane of TNBC cells and ROS to induce apoptosis, but also provided a suitable opportunity for imaging by reducing hypoxia. Similarly, it was determined that the use of PDT effectively increases the rate of O 2 release by CeO 2 NZ containing Cinobufagin (Zeng et al 2022). Sustained supply of O 2 led to greater drug penetration, reduced cell migration, and reduced TNBC tumor size in a mice model.…”
Section: Introductionmentioning
confidence: 99%